Complex and creative intimate and sexual citizens: mapping a study that seeks to understand children outside the binary of sexual innocence or sexual contamination. Issue 5 (2nd September 2016) - Etheredge, L. R.
Abstract: This paper explores the rationale for an empirical study that examines the way children interpret the intimate relationships they experience in digital spaces. The design of the study recognizes children as agentic intimate and sexual citizens who are capable of documenting their thoughts and understandings in creative and entertaining ways through the construction of short films. To this end, the study acknowledges that sexuality is important in the lives of children while also highlighting the limitations that exist when sexuality, children, digital spaces and educational sites intersect. In response to this positioning, the study seeks to understand children's experiences of the broader continuum of intimate relationships rather than a singular focus on sexuality. In developing this study, it has become clear that there are many boundaries that impede discourses, learning and explorations in educational spaces around the performative explorations and intimate investigations of children conducted in and through digital spaces.